Nationalist and Religious-Based Superior Kindergarten Curriculum Management - Zeni Uswatun Hasanah; Fatah Syukur; Nur Uhbiyati (ARKA INSTITUTE, 2022)
Curriculum management study as a milestone in curriculum success ais important to be carried out as early as possible, considering that early age is a crucial period in shaping children’s character so that it becomes achy or foundation when children grow up. This is the basis for conducting research on nationalist and religious-based kindergarten curriculum management.This paper uses the library research method. The Result of this study that nationalist and religious-based kindergarten are special education for children with an age range of 4 to 6 years which emphasizes the values of nationalist and religious in each program. There are four(4) nationalist and religious-based kindergarten curriculum management procedures, namely planning, organizing, implementing and evaluating.